Assessing inoculation’s effectiveness in motivating resistance to conspiracy propaganda in Finnish and United States samples - Bessarabova, Elena; Banas, John A.; Reinikainen, Hanna; Talbert, Neil; Luoma-aho, Vilma; Tsetsura, Katerina (Frontiers in Psychology, 2024)
This study tested the motivational power of inoculation to foster resistance to conspiracy propaganda (9/11 Truth Movement), comparing inoculation effects across U.S. and Finnish study participants. We used a 2 inoculation (treatment vs. control) × 2 national culture (American vs. Finnish) independent groups design (N = 319), while examining the effects of motivational threat and thinking modes-analytic vs. intuitive-on the inoculation process. To test the effectiveness of the inoculation strategy, we used an excerpt from a conspiracy film Loose Change as a counterattitudinal attack message. Our results indicated that inoculation was effective at motivating resistance regardless of national culture. Inoculation effects emerged mostly as a direct effect on resistance and two indirect effects wherein motivational threat mediated the relationship between inoculation and resistance as well as resistance and analytic mode of message processing. Although we found that an increase in analytic mode of processing facilitated resistance and intuitive processing increased conspiracy theory endorsement, the indirect effects between inoculation and resistance via message processing modes were not significant. Finally, the data revealed national culture differences in analytic mode and cultural-context differences, mostly pertaining to the relationships between thinking styles, media literacy and modes of thinking. These results offer important theoretical implications for inoculation scholarship and suggest viable practical solutions for efforts to mitigate misinformation and conspiratorial beliefs.